Interlending and Document Supply Services at Qatar National Library: A Focus on Multicultural Patron Engagement and Enhancement - Rowena O. Aquino (20893523) (2024)
The paper explores the landscape of Interlending and Document Supply (ILDS) services at Qatar National Library (QNL) with a focus on patron demographics, collection diversity, and topic preferences, particularly in cultural and ethnic studies. Analysis reveals the distribution of patrons across various institutions, with a concentration from educational and professional sectors. The paper delineates partner institutions and aims to identify regions of high patron engagement, indicating potential areas for strategic collaboration. Furthermore, it examines the diversity of collections accessible through ILDS highlighting the prevalence of requests of materials pertaining to culture, history, and ethnic studies. Data indicates a portion of requested articles and titles falling within this thematic domain, emphasizing its importance to patrons. This paper also evaluates the current status of cultural and ethnic studies within the ILDS framework and proposes strategies for enhancement. Recommendations include targeted acquisitions, fostering partnerships with institutions specializing in these areas, and advocating for the inclusion of diverse perspectives in collection development policies. Ultimately, the paper underscores the significance of cultural and ethnic studies within ILDS Services at QNL and offers actionable insights for future improvements and advocacy efforts. Other Information Conference information: 18th IFLA ILDS Interlending and Document Supply Conference : Global to Local: Diversity and Inclusiveness in Resource Sharing - ADA University; Baku, Republic of Azerbaijan, December 02-04, 2024 License: http://creativecommons.org/licenses/by/4.0/ See program on conference's website: https://ilds.ada.edu.az/program/conference-program